PENANGANAN BENCANA BERBASIS KOMUNITAS MELALUI PROGRAM DESA TANGGUH BENCANA DI DESA GARON KECAMATAN BALEREJO KABUPATEN MADIUN - Widya Permana, Mahar; Endi Rahman, Nuril (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2023)
Disaster situations require new strategies that are relevant to the problem context. The Disaster Resilient Village Program (Destana) is a disaster management effort that uses a Community-Based Disaster Risk Management (PRBBK) strategy. This research aims to look at implementing the Destana program in Garon Village, Balerejo District, Madiun Regency. This research method uses descriptive qualitative, data mining techniques using in-depth interviews, observation, and documentation studies. The research results show that the implementation of the Destana program in Garon Village has not demonstrated a Community-Based Disaster Management approach, considering that there is no active participation from the community in the entire disaster management series. Community capacity in disaster management is also still not visible because there is no community organization, in this case, the community is still used as an object. The preparedness of the Garon Village community is still low in facing flood disasters, due to the lack of active community participation in the program. Thus, program managers need evaluation so that the approach used can be implemented substantively, and community capacity can be increased in dealing with disaster situations. Keywords: Disaster, community-based disaster, community organization